Decolorization of Metal-Complex Dye Direct Blue-86 in Wastewater by Potassium Ferrate(VI) - Lei, B.; Zhou, G.D.; Mi, H.B.; Zhen, K.J.; Cheng, T.X. (Asian Journal of Chemistry, 2011)
Study on decolorization of metal-complex dye direct blue-86 in wastewater by potassium ferrate(VI) was carried out. Effects of pH value, oxidant dose, reaction time, initial concentration of dye and temperature on the decolorization were examined. In the absorption spectra during the decolorization process, it is clearly observed that Cu-phthalocyanine macrocycle in direct blue-86 can easily be destroyed by potassium ferrate(VI). Compared with the decolorization, the removal percentage of COD and total organic carbon were only 10.22 and 59.70 % after 1 h, respectively. It indicates that the complete mineralization of direct blue-86 cannot be achieved under oxidation by potassium ferrate(VI).